Point-of-Care Ultrasound to Identify the Source of Dyspnea in a Patient With Systemic Lupus Erythematosus. Issue 3 (March 2019) - Lee, Horton J.; Budhathoki, Rasmita
Abstract : Abstract: Point-of-care ultrasound can be used to help identify the source of dyspnea in patients presenting to the emergency department. We present a case of an adolescent girl with a history of systemic lupus erythematosus presenting to the emergency department with chest pain and dyspnea and found to have both pleural and pericardial effusions on point-of-care ultrasound. Abstract : Supplemental digital content is available in the text.